2020
DOI: 10.1021/acsphotonics.0c01350
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution without Imaging: Library-Based Approaches Using Near-to-Far-Field Transduction by a Nanophotonic Structure

Abstract: Super-resolution imaging is often viewed in terms of engineering narrow point spread functions, but nanoscale optical metrology can be performed without real-space imaging altogether. In this paper, we investigate how partial knowledge of scattering nanostructures enables extraction of nanoscale spatial information from far-field radiation patterns. We use principal component analysis to find patterns in calibration data and use these patterns to retrieve the position of a point source of light. In an experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Unraveling the physics of directivity control does therefore require the measurement of radiation patterns with Fourier microscopy of individual nanosources that are pinpointed in space by a super-resolution technique. It was recently shown that this idea can even be reversed: once a library of radiation patterns as a function of position is measured, one can reconstruct the location of source to within 10 nm precision simply by analyzing its radiation pattern (radiation-pattern-based localization microscopy) [113].…”
Section: Nanophotonic Parameters Of Interest For Super-resolution Ima...mentioning
confidence: 99%
“…Unraveling the physics of directivity control does therefore require the measurement of radiation patterns with Fourier microscopy of individual nanosources that are pinpointed in space by a super-resolution technique. It was recently shown that this idea can even be reversed: once a library of radiation patterns as a function of position is measured, one can reconstruct the location of source to within 10 nm precision simply by analyzing its radiation pattern (radiation-pattern-based localization microscopy) [113].…”
Section: Nanophotonic Parameters Of Interest For Super-resolution Ima...mentioning
confidence: 99%
“…The second main ingredient is that we use a highly efficient representation of the library of radiation patterns to facilitate the comparison between test and library data. This representation of the measured radiation patterns uses singular value decomposition, as previously used to localize a point source of light [17]. We note that, alternatively, the comparison between test and library data could be a task suitable to address with machine learning, provided that the library data set is sufficiently large -typically orders of magnitude larger than the number of parameter values to be distinguished.…”
Section: Localization Strategymentioning
confidence: 99%
“…Next, we calculate the match of newly acquired data A at positions i with the reference data at positions j, which we define as 1 − ‖(UΣ) j − A i V‖∕ √ 2. A high match indicates high similarity between radiation patterns [16,17]. To obtain an estimate for the object position based on the measured radiation patterns, we take the reference position that is associated with the highest match as the retrieved position.…”
Section: Localization Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…However, fluorescence‐based techniques are limited to sparsely distributed sources and scanning probes have very simple and small exposure or collection volumes that necessitate slow, point‐by‐point raster‐scanning measurements. Modern inverse design approaches to computational imaging and parameter retrieval [ 20–23 ] defeat these constraints by careful modelling. Yet, these methods take up either additional complexity to account for their limited knowledge of exposure field patterns or the requirement of detailed a priori knowledge on the family of structures under study.…”
Section: Introductionmentioning
confidence: 99%